Pete the kitty and the unicorn's missing colors ebook - Dean, James (My First I Can Read: Pete the Kitty., 2020)
A magical unicorn adventure from New York Times bestselling creators Kimberly and James Dean! Pete the Kitty's friend Stevie the unicorn somehow lost all the colors in her rainbow tail. It's a good thing Pete has his magical paintbrush to help out. Together, they search for the missing colors of the rainbow. Young unicorn fans will love Pete's enchanting adventure in this My First I Can Read story, complete with original illustrations from the creator of Pete the Cat, James Dean. My First I Can Read books are perfect for shared reading with a child. Books at this level feature basic language, word repetition, and whimsical illustrations, ideal for sharing with emergent readers. The active, engaging stories have appealing plots and lovable characters, encouraging children to continue their reading journey.